Socialization of Characterization and Molecular Identification of Protease Enzyme-Producing Bacteria from Tempeh Traded in Lubuk Pakam Market - Krisdianilo, Visensius; Bukit, Sari Theresia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2023)
Enzymes are an important ingredient in industry and health. There are several types of enzymes that are widely used by humans such as cellulase enzymes, lipase enzymes, amylase enzymes and protease enzymes. Protease enzymes are enzymes that can accelerate the breaking of protein peptide chains. This enzyme is one of the most widely used enzymes in the industry with sales value reaching 60% of world enzyme sales. Very many industrial products use enzymes with enzyme demand that continues to increase. Total sales of enzymes in the industry in 2010 reached 3.3 billion US dollars and will continue to increase in the coming years.Protease enzymes can be isolated from plants, animals and microorganisms. The use of microorganisms in producing protease enzymes is very potential due to the very fast growth of microorganisms and can be grown on fairly cheap media. The purpose of this socialization is to provide information related to the examination of bacterial molecules producing protease enzymes in tempeh. From the activities carried out, it can be concluded that the presence of bacteria in tempeh sample S-2 which has the largest diameter is identical to the bacterium Pseudomonas stutzeri, while from the results of the participants' understanding, the results of the pre-test dominant understanding are sufficient (60%) and the results of the post-test results are dominantly good understanding (67%) which means that seminar participants are able to understand the material presented.